Investigation of electric field driven crystallization of phase change materials - Yeow, Susan Su Yi (2016)
Chalcogenide phase change material is based on the fast reversible switching between an amorphous and a crystalline phase. This switching phenomenon is an important characteristic of phase change material. However, understanding of this mechanism is not completely clear. This is particularly so for electrically driven phase change memory where a certain threshold voltage needs to be exceeded to enable sufficient current to flow through the phase change cell for crystallization to occur. Moreover, one of the important properties for memory storage capability is the high switching speed. Since crystallization of phase change material is the time limiting step in storage application a detailed understanding of the fast crystallization process is essential for the design of¬ even faster materials. Hence, it would be useful to find out the influence of electric field on the enhanced crystallization behaviour and the mechanism for electric field driven crystallization. Sub-threshold were applied and the amount of joule heat was evaluated by COMSOL simulation and thermo-reflectance imaging. This is to ensure that the current induced minimal joule heating, as excessive joule heating could dominate the electric field driven crystallization. The study was first carried out by isothermal electrical experiments to evaluate the crystallization time under an applied electric field. It was found that crystallization time was accelerated by the applied electric field. TEM analysis for different stages of crystallization under the applied electric field was conducted to deepen the understanding of the crystallization behaviour. Nuclei were predominantly observed at the interface which leads to the surface roughness investigation. It was proposed that rougher surfaces could boost crystallization by the electric field enhancement. The activation energy for rougher surface derived from the Kissinger plot appeared lower than the smoother surface. In addition. from the TEM analysis, the crystal formation was visualized to form layer-wise with a parallel orientation to the electric field direction mechanism. Investigation proceeded to establish the electric field driven crystallization. The electric field dependent activation energy of crystallization was evaluated. The measurement shows that the applied electric field lowers the energy required for crystallization. Classical crystallization equation was also modified which showed negative Gibbs free energy under electric field implying electric field favours crystallization. This dissertation has shown the influence of an applied electric field on the crystallization of phase change material by studying electric field applied below the threshold and these findings provide the fundamental understanding of electric field driven crystallization of phase change material.